Documentation and Conservation of Wild Edible Plants in Ado- Ekiti Region of Ekiti State, Nigeria - Kayode, J.; Akinluyi, S. M. (Canadian Journal of Agriculture and Crops, 2016)
A survey of wild edible plants was carried out in Ado-Ekiti region with the aim of documenting wild edible plants species (WEPs) in the study area, determine their abundance and propose strategies that would help in the conservation of the rare species. A rapid appraisal method was used. Visits were made to four randomly selected communities in the region where semi-structured questionnaire guide was used to elicit information from the respondents. Interviews were also carried out with groups of respondents as well as key informants. A total of 47 WEPs which belonged to 32 families were identified in the region. The various ethnobotanical utilizations of the WEPs were defined. The species were not cultivated hence respondents depended on wildlings of the species. The abundance scale used in this study revealed that 10 of the WEPs were presently rare. Strategies that would conserve the rare species were proposed.